A Dufour bladelet from Potočka zijalka (Slovenia) - Odar, Boštjan (Arheološki vestnik, 2008)
At one of the most important Aurignacian sites in Europe, the cave of Potočka zijalka, part of a bladelet of the Dufour type was recently discovered. It was lying on the surface of the heap of sediments excavated by Srečko Brodar in the years 1928–1929 in the rear of the cave. Potočka zijalka is known primarily for the 125 bone points and 11 other bone tools found there in a perfect state of preservation and bearing the age of approximately 30,000 years. It is interesting to note that almost contemporaneously with the appearance and use of the bone points from Potočka zijalka, the nearby cave site of Vindija in Croatia was used by the Neanderthals, the bone remains of which were uncovered in the youngest Mousterian G1 complex of Vindija together with bone points